(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Background: The Achilles tendon is one of the most commonly ruptured tendons in the human body. Though closed Achilles tendon injury is common in developed countries as it occurs in sports injury, on the contrary, open Tendo-Achilles injury is the most common type of injury in developing countries like Bangladesh. Objective: To assess the demographic and injury characteristics of Tendo-Achilles (TA) injury. Methods: This Prospective observational study was carried out among 50 patients attending at the Department of Orthopaedics, Cumilla Medical College Hospital, Cumilla from January 2022 to December 2022. Ethical clearance was obtained from the Institutional Review Board (IRB) of Cumilla Medical College Hospital. Purposive sampling was done according to availability of the patients. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: The mean (±SD) age of the patients were 29.48±13.53 years. More than two-thirds of the patients 34(68.0%) were male, whereas 16 (32.0%) were female. In terms of comorbidity, DM was detected in 2 (4.0%), HTN in 2 (4.0%) and HTN+DM+COPD in 1 (2.0%). The Sharp edge of broken toilet pan was the most prevalent cause of injury 19(38.0%), followed by sharp cut 13(26.0%), tin sheet 10(20.0%), RTA 5(10.0%), digging hoe 2(4.0%), and machinery 1(2.0%). Almost two-thirds 32(64.0%) of patients had a cut level from calcaneal insertion of 3-4 cm, with 31 (62.0%) having involvement on the right side. Conclusion: Tendo-Achilles injury in the Bangladesh most commonly occur in young male patients (20-39 years old), with participation in recreational sports being the most likely mechanism. Recognizing high-risk patients can help physicians counsel them and recommend strategies for injury prevention. J. Dhaka National Med. Coll. Hos. 2024; 30 (02): 36-38